Reliability and Validity of the Quick Inventory of Depressive Symptomatology—Self-Report Scale in Older Adults With Depressive Symptoms - Liu, Rui; Wang, Fei; Liu, Shou; Zhang, Qinge; Feng, Yuan; Sim, Kang; Cui, Xiling; Lin, Jing-Xia; Ungvari, Gabor S.; Xiang, Yu-Tao (Frontiers in Psychiatry, 2021)
Background: Depressive symptoms are common in older adults. Developing rapid self-report tools is essential to measure the presence and severity of depressive symptoms in older adults. This study evaluated the psychometric properties of the Quick Inventory of Depressive Symptomatology- Self-Report (QIDS-SR) scale for use in depressed older adults. Methods: A total of 238 depressed older adults were included in the study. The Montgomery-Asberg Depression Rating Scale (MADRS) and the QIDS-SR were administered to assess the severity of depressive symptoms. Cronbach’s alpha coefficient, Spearman rank correlations and principal component analysis were performed to estimate the internal consistency, concurrent validity and factorial structure of the QIDS-SR, respectively. Results: The Cronbach’s alpha for the QIDS-SR was acceptable (α=0.64). Item-total correlation analyses showed that the items of concentration/decision, involvement, energy level, and agitation/retardation had high correlation with the QIDS-SR total score (all correlation coefficients ≥ 0.60). The QIDS-SR total score was significantly correlated with the MADRS total score (r=0.53, p<0.001), demonstrating acceptable concurrent validity. Factor analysis revealed the unidimensional structure of the QIDS-SR. Conclusions: The QIDS-SR appears to be a reliable and valid self-report scale for estimating the severity of depressive symptoms in depressed older adults.